Implementation of the Guided Inquiry Learning Model Based on Ethno-STEM Terasi Udang to Improve Students' Science Process Skills - Fadhillah Khoirunisah; Beni Setiawan; Mohammad Romadhoni (Jurnal Pemberdayaan Masyarakat, 2026)
This study aims to describe improvements in students' science process skills and the implementation of guided inquiry-based learning using Terasi Udang as a medium in the context of Ethno-STEM. The research design is a one-group pretest-posttest design. The subjects in this study were 33 students in class IX-E at SMP Negeri 1 Prambon. The instruments used in this study were pretests and posttests of science process skills and an observation sheet for the implementation of teacher activities. The improvement in science process skills was analyzed using N-Gain analysis and the Wilcoxon test, while the implementation of teacher activities was analyzed using the Guttman scale. Students' science process skills improved after implementing the Guided Inquiry learning model based on Ethno-STEM. The research results regarding science process skills were evidenced by an average N-Gain score of 0.73, categorized as High, and by a p-value of 0.000 ( 0.05) from the Wilcoxon test. Since the p-value was 0.05, H0 was rejected, and H1 was accepted. The implementation of the learning process achieved a 100%. This study contributes to science education by demonstrating that the Etno-STEM approach is an effective strategy for enhancing learning quality.